182k views
2 votes
In the figure below, m∠JKM = 73° , m∠LKM = 40°, and line KN bisects ∠LKM. Find m∠JKN.

In the figure below, m∠JKM = 73° , m∠LKM = 40°, and line KN bisects ∠LKM. Find m∠JKN-example-1
User Qster
by
3.9k points

1 Answer

6 votes

From the diagram we can conclude:


m\angle JKM=m\angle JKL+m\angle LKN+m\angle NKM

Since KN bisects bisects ∠LKM:


\begin{gathered} m\angle LKN=m\angle NKM \\ so\colon \\ m\angle LKM=2m\angle LKN \\ m\angle LKN=(m\angle LKM)/(2) \\ m\angle LKN=(40)/(2) \\ m\angle LKN=20 \end{gathered}

Therefore:


\begin{gathered} 73=m\angle JKL+20+20 \\ m\angle JKL=73-20-20 \\ m\angle JKL=33 \end{gathered}

Hence:


\begin{gathered} m\angle JKN=m\angle JKL+m\angle LKN \\ m\angle JKN=33+20 \\ m\angle JKN=53 \end{gathered}

User Zhao Xiang
by
4.6k points